Prevalence and diagnosis of Chlamydia trachomatis in women of childbearing age. A systematic review (Research, Society and Development, 2025)
Globally, Sexually Transmitted Diseases (STD) are a public health problem involving thousands of people each year, among the most prominent of which is Chlamydia trachomatis (Ct), which is the most commonly reported bacterial STD in countries around the world. This is an obligate intracellular microorganism that affects cells in the genital tract. The object was to construct a literature review on the issue of prevalence and diagnosis of Ct in women of childbearing age. The methodology is framed as a systematic review in which specialized databases such as ScienceDirect, Pubmed, Scopus, Web of Science, Lilacs and Scielo were used, with a horizon from 2019 to 2024, creating a search formula with boléanos and keywords (women of childbearing age, prevalence, epidemiology and diagnosis). Result: 7 registries were chosen which have information on the subject in terms of prevalence and diagnosis for Ct. The most important countries were Chile, France, Kenya, Iran and the United Kingdom, also highlighting methods such as PCR, NAAT, RDT Based on Immunoassay, Serology, Autotome and Urinary Tests with Combined PCR. Conclusions: the prevalence of Ct varies according to the geographical context as well as the population context, it is important to underline the needs in the implementation of new methods for the detection of Ct.